'The scourge of the stones': English gunpowder artillery at the siege of Harfleur. Issue 1 (1st January 2017) - Spencer, Dan
ABSTRACT: In 1415, the army of Henry V of England succeeded in capturing the French town of Harfleur after a six-week siege. This was a watershed moment in the history of warfare, as it was the first time that an English army had made extensive use of gunpowder weapons in besieging a sizeable urban settlement. Firearms were subsequently used in all major military operations, playing a key role in siege warfare and soon completely superseding traditional mechanical artillery. This paper examines the reasons why this important technological change occurred in the early fifteenth century and assesses the effectiveness of the English guns during the siege.